Adjectival vs verbal syntax: a case study from Ancient Greek (Atti del Sodalizio Glottologico Milanese, 2017)
This paper focuses on verbal adjectives that have the affix -τέο- and deontic value. By adopting a syntactic point of view, the constructions with verbal adjectives are compared with those having the corresponding verbs and are found to be different regarding the organization of syntactic functions. In particular, the notional subject can occur as a grammatical subject in verbal constructions, but it never occurs as the grammatical subject in adjectival constructions. A new analysis will be suggested, concerning the relationship between the lexical categories of predication (verb, adjective) and the syntactic functions. KEYWORDS: verbal adjectives, Ancient Greek, grammatical relations, dative of agent, personal and impersonal constructions